Synovial sarcoma presenting as subcutaneous swelling: a rare presentation - Kalwaniya, Dheer S.; Bajwa, Jaspreet S. (International Surgery Journal, 2019)
Synovial sarcoma unlike its name is not originating from synovial cells. It accounts for approximately 10% of all soft tissue sarcomas with main predilection for extremities.We present here a case of synovial sarcoma of subcutaneous origin of knee joint which is rarest of presentations and early diagnosis is associated with lower risk of metastasis and hence better prognosis.